KEBIJAKAN HUKUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA ASUSILA (ANALISIS PUTUSAN PN LUBUK PAKAM NO:40/PID.SUS-ANAK/2018/PN.LBP) - P.A Juanda Panjaitan; Triono Edy (JURNAL DOKTRIN REVIEW, 2022)
Immoral crimes or immoral crimes include crimes such as: sexual intercourse, rape, obscenity, and so on are crimes that are currently very troubling for the Indonesian people, especially for women. minors and is also carried out by children who also need the legal protection of children's rights. Legal Regulations Against Children as Perpetrators in Immoral Crimes. The regulation of immoral crimes is regulated in Law no. 35 of 2014 is regulated in Article 76D, Article 76E, and criminal penalties for these acts are regulated in Article 81, and Article 82. The enactment of Law no. 11 of 2012. regulates several provisions regarding children in conflict with the law including the definition and age of the child, penalties/sanctions imposed on children as perpetrators of criminal acts, detention of children as perpetrators of criminal acts, examination of children as witnesses or victims, the right to obtain legal assistance. for children involved in the law, special child correctional institutions, diversion efforts based on restorative justice by law enforcement officers.